Anti-NS1 protein of influenza virus: a potent anti-viral strategy: Anti-NS1 protein of influenza virus: a potent anti-viral strategy - Pushparaj, Samuel (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Influenza viruses are potent pathologic agents that cause lethal respiratory disease worldwide. The nonstructural protein (NS1) protein of the influenza virus plays a vital role in the virus replication by the evasion of host innate immune system. NS1 protein was found to be conserved functionally in both Influenza A and B viruses. Recent studies revealed that the NS 1 protein of influenza A and B viruses binds to TRIM 25 ubiquitin ligase that is needed for the post-translation modification of the RIG-I and thereby prevents the interferon signaling cascade. Protacs are the bifunctional molecules that bind to the target protein and an ubiquitin ligase, enabling ubiquitination and destruction of the target protein through the Ubiquitin-Proteasome system. In this minireview, based on earlier studies we propose novel molecules designed to target NS1 protein in order to elicit an interferon response and NEDD4 ligase to prevent the degradation of interferon (IFN)-induced transmembrane protein 3 (IFITM3).